Fallopian Tube Torsion as a Cause of Acute Pelvic Pain in Adolescent Females - Claudia Mueller; Sandra Tomita (Case Reports in Pediatrics)
Purpose. Torsion of the fallopian tube, involving hydatids of Morgagni, though a rare cause of acute pelvic pain in young girls, can pose significant risks to future fertility. Tubal torsion may present as a diagnostic dilemma since the ovary itself usually appears normal on ultrasound. Thus, surgical intervention may be delayed which can lead to worsening necrosis and result in the need for resection of the affected tube. Methods. We reviewed two cases of fallopian tube torsion associated with hydatids of Morgagni in adolescent females. Results. The patients were premenarchal in both cases, aged 10 and 13 years. Both presented with acute clinical signs of ovarian torsion but ultrasound showed the ovary itself to be normal with an adjacent cystic structure. In both cases, the fallopian tube was detorsioned laparoscopically and preserved. The associated cyst was excised in one case and marsupialized in the other. Conclusions. We propose that prompt recognition and operative management of this relatively uncommon source of pelvic pain may prevent unnecessary tubal resection and improve long-term fertility in this population.